2017
DOI: 10.1080/15438627.2017.1282357
|View full text |Cite
|
Sign up to set email alerts
|

The age of the best ultramarathon performance – the case of the “Comrades Marathon”

Abstract: The aim of the present study was to determine the age of the fastest running speed in 202,370 runners (34,090 women and 168,280 men) competing in the "Comrades Marathon" between 1994 and 2015 using non-linear regression analysis (second order polynomial function). When all runners were considered in 1-year age intervals, the fastest running speed (9.61 ± 1.65 km/h) was achieved at the age of 29.89 years in men, whereas women achieved it at the age of 35.96 years 8.60 ± 1.10 km/h. When the fastest runners were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Furthermore, analyses reveal in Figure 6, that Napfmarathon with a regression weight of β = 0.0369 is smaller than in city marathon with β = 0.0487, in line with the before mentioned and implying, that the decrease in physical endurance performance in Napf marathon is smaller compared to city marathons. Besides other reasons the simple fact of the total larger amount of performance is probably one important reason [3,7,8,11,22]. The meter above sea level of the race (700 to 1400 Meter) respectively the effect of a smaller oxygen pressure doesn`t seem to be relevant while analyzing differences (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, analyses reveal in Figure 6, that Napfmarathon with a regression weight of β = 0.0369 is smaller than in city marathon with β = 0.0487, in line with the before mentioned and implying, that the decrease in physical endurance performance in Napf marathon is smaller compared to city marathons. Besides other reasons the simple fact of the total larger amount of performance is probably one important reason [3,7,8,11,22]. The meter above sea level of the race (700 to 1400 Meter) respectively the effect of a smaller oxygen pressure doesn`t seem to be relevant while analyzing differences (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Studies tax the decrease of endurance capacity after the 30. Year of life with 15 % per decade [5][6][7][8]. To keep in mind with increasing distance the optimum of maximum distance is based on adaptations while years through training higher [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Year of life with 15 % per decade to keep in mind with increasing distance the optimum of maximum distance is based on adaptations while years through training higher [5][6][7][8]. The detected optimal age for middle distances is between 20 and 30 years, for marathon races around 35 years and increases to 40 or more years for ultra-races [8][9][10][11]. Addressing changes in general endurance performance in leisure sports men for marathon running analysis of the big sample of over 900`000 course times revealed that for 20-to 79-year old marathon and half-marathon runners that interestingly no significant decrease based solely on age could be detected respectively decrease was mainly a result of physical inactivity [1].…”
mentioning
confidence: 99%